1988
DOI: 10.1111/j.1365-2621.1988.tb08984.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solute Type on Sorbate Resistance in Zygosaccharomyces rouxii

Abstract: The effect of sorbate on the growth of Zygosaccharomyces rouxii was evaluated at reduced a, using sucrose, glucose and polyethylene glycol (PEG). Sorbate-adapted and unadapted cells were grown aerobically at pH 5.0 in media adjusted to 0.92 a, by addition of the solutes. Sorbate resistance by unadapted cells increased in the order of glucose < PEG c sucrose. Solute type had little effect on sorbate resistance by sorbateadapted cells in media containing glucose and sucrose. The combination of PEG and 400 &mL so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…The latter can grow in the presence of 600 mg/L of sorbic acid and at pH levels less than the pKa of the preservatives (Warth, 1977). The yeast growth and its sorbate resistance could be affected by the type of solute used to reduce the water activity (a w ) as well as by other solutes present in the food (Lenovich, Buchanan, Worley, & Restaino, 1988). For these reasons, Z. bailii is a major concern to manufacturers of acidic products.…”
Section: Introductionmentioning
confidence: 98%
“…The latter can grow in the presence of 600 mg/L of sorbic acid and at pH levels less than the pKa of the preservatives (Warth, 1977). The yeast growth and its sorbate resistance could be affected by the type of solute used to reduce the water activity (a w ) as well as by other solutes present in the food (Lenovich, Buchanan, Worley, & Restaino, 1988). For these reasons, Z. bailii is a major concern to manufacturers of acidic products.…”
Section: Introductionmentioning
confidence: 98%
“…Sorbitol, xylitol and mannitol reduce or do not promote the risk of tooth decay, which causes less increase in the blood sugar and insulin levels than carbohydrates, and act as humectants, thus depressing the water activity and inhibit the yeast growth (Lenovich et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The combined use of KS and heat exerts a synergistic lethal effect on yeasts (Makdesi & Beuchat, 1996). In relation to the solute used as humectant, it was reported that polyols and sugars increase the heat resistance of bacteria, yeast and fungal spores (Corry, 1976a(Corry, , 1976bLenovich et al, 1988;Smith, Benedict, Haas, & Palumbo, 1983). But this behavior depends on solute used as humectant and on the nature of the microorganism (Almagro et al, 2000).…”
Section: Introductionmentioning
confidence: 96%
“…bailii is able to grow at a pH as low as 2.2 and in the presence of 600-750 mg/L of sorbic (Praphailong & Fleet, 1997; Thomas & Davenport, 1985). However, this abilities can be affected by the acidification agent, the solute used to reduce the a w as well as by other solutes present in the food (Lenovich, Buchanan, Worley, & Restaino, 1988;Thomas & Davenport, 1985).…”
Section: Introductionmentioning
confidence: 97%